Effects of feeding excess crude protein on growth performance and carcass traits of finishing pigs - S M Williams; C Feoli; S Issa; Terry L Gugle; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2008)
A total of 176 pigs (88 barrows and 88 gilts, average initial BW of 209 lb) were used in a 33-d experiment to determine the effects of excess dietary CP on growth performance and carcass measurements of finishing pigs. Pigs were sorted by sex and ancestry and blocked by weight with 11 pigs per pen and 4 pens per treatment. Treatments were corn-soybean meal based and formulated to a minimum of 0.80% total lysine but with 12, 14, 16, and 18% CP. Feed and water were consumed on an ad libitum basis until pigs were slaughtered (average final BW of 275 lb) at a commercial abattoir. Increasing CP concentration had no effect (P>0.20) on ADG, ADFI, F/G, and HCW. With HCW used as a covariate, there were linear decreases in dressing percentage (P<0.01) and loin depth at the last rib (P<0.04) as CP concentration in the diet was increased from 12 to 18%. However, fat thickness at the last rib and percentage carcass lean were not affected (P>0.34) by CP treatment. Our results indicate that increasing CP from 12 to 18% in diets for late-finishing pigs does not affect growth performance or carcass leanness but has small negative effects on dressing percentage and loin depth.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Carcass; Finishing pigs; Growth; Protein